2015
DOI: 10.1111/papr.12288
|View full text |Cite
|
Sign up to set email alerts
|

Unsuccessful Pulsed Radiofrequency of the Sphenopalatine Ganglion in Patients with Chronic Cluster Headache and Subsequent Successful Thermocoagulation

Abstract: We present the results of pulsed and continuous radiofrequency (CRF) of the sphenopalatine ganglion in a case series of 3 patients with chronic cluster headache (CCH). Three patients were referred to our neurosurgical department because of CCH, which was refractory to pharmacological treatment. They underwent pulsed radiofrequency of the sphenopalatine ganglion (PRF-SPG), and the procedure was performed through an infrazygomatic approach. In the PRF procedures, we applied 2 cycles of PRF at 42°C and 45 V for 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…These techniques have different mechanisms of action at the target site. Bendersky et al illustrated this when they published a case series in which three patients had partial relief with PRF but experienced complete symptom resolution with a subsequent RFA 2 months after their initial intervention with PRF [28].…”
Section: Review Of Clinical Datamentioning
confidence: 95%
“…These techniques have different mechanisms of action at the target site. Bendersky et al illustrated this when they published a case series in which three patients had partial relief with PRF but experienced complete symptom resolution with a subsequent RFA 2 months after their initial intervention with PRF [28].…”
Section: Review Of Clinical Datamentioning
confidence: 95%
“…Complete pain relief was observed in 2 patients with ECH and CCH, and the other patient with CCH received partial relief after the PRF procedure. In contrast, in 2015, Bendersky et al reported that SPG‐PRF under lateral fluoroscopy guidance was unsuccessful. Only 1 of 3 patients with CCH achieved PR after SPG‐PRF, and poor efficacy was shown in the other 2 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, PRF is expected to be a first‐line treatment for patients with refractory CHs who have not responded to or cannot tolerate drug treatments. However, Bendersky et al counterargued that the efficacy of PRF for CCH is insufficient. Therefore, further studies are needed to evaluate whether SPG‐PRF is a promising treatment for CHs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, going beyond the actual management of CH, VNS seems to be promising but is still classified at Class IV evidence [21], while sphenopalatine ganglion stimulation shows contrasting evidence [29,30] that needs to be confirmed and validated through RCTs.…”
Section: Beyond the Reliable Pharmacological Triadmentioning
confidence: 99%